IDENTIFIKASI AMFETAMIN PADA URINE SOPIR ANGKOT DI PAJAK HORAS PEMATANGSIANTAR - Salim, Sarnia; Aruan, Dyna Grace Romatua (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The prevalence of drug abuse is quite high in Indonesia in the land transportation sector, including public transportation. Amphetamines are among the most widely used drugs in the community which are included in the Psychotropic class II. Amphetamines are also a group of drugs that stimulate the central nervous system, which can affect the brain's cortex to increase mental activity. Amphetamines can trigger the release of several neurotransmitters in the body, such as dopamine, norepinephrine, and serQotonin. The increase caused by these neurotransmitters can increase energy stimulation, increase physical endurance, motor activity, and cause a feeling of pleasure. All organs in the body work harder, so users feel more focused, empowered, confident and able to think quickly. The effect of using amphetamine is that it can eliminate fatigue and drowsiness. The aim of the study was to determine whether the content of amphetamine compounds was present in the urine samples of public transportation drivers at the Horas Pematangsiantar Tax. The sampling location was carried out at the Pematangsiantar Horas Tax while the research location was carried out at the Simpang Bah Jambi Health Center. The type of research used is qualitative data research which is described descriptively using a stick test tool with the Immunoassay method which was carried out in May 2023. The examination results of 50 samples were negative. The conclusion based on the results of the examination was that there was no amphetamine content or negative results in the urine of public transportation drivers at the Horas Pematangsiantar Tax.